2020
DOI: 10.5056/jnm19032
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Pepsin as an Intrinsic Marker for Diagnosis of Sub-types of Gastroesophageal Reflux Disease and Gastroesophageal Reflux Disease-related Disorders

Abstract: Background/AimsTo determine the value of salivary pepsin in discriminating sub-types of gastroesophageal reflux disease (GERD) and GERD-related disorders. MethodsOverall, 322 patients with different sub-types of GERD and 45 healthy controls (HC) were studied. All patients took Gastroesophageal Reflux Disease Questionnaire (GerdQ) and underwent endoscopy and 24-hour esophageal pH monitoring and manometry. Salivary pepsin concentration (SPC) was detected by using colloidal gold double-antibody immunological sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 56 publications
0
34
0
8
Order By: Relevance
“…The study showed that salivary pepsin concentration was higher in erosive esophagitis, nonerosive reflux disease (NERD), and extraesophageal symptoms compared than healthy controls. 1 No significant difference was found in the positive rate for pepsin in patients with functional heartburn or GERD with anxiety and depression (GERD-AD) compared to healthy controls. 1 Proton pump inhibitors reduced salivary pepsin concentration in patients with NERD and extraesophageal symptoms.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…The study showed that salivary pepsin concentration was higher in erosive esophagitis, nonerosive reflux disease (NERD), and extraesophageal symptoms compared than healthy controls. 1 No significant difference was found in the positive rate for pepsin in patients with functional heartburn or GERD with anxiety and depression (GERD-AD) compared to healthy controls. 1 Proton pump inhibitors reduced salivary pepsin concentration in patients with NERD and extraesophageal symptoms.…”
mentioning
confidence: 93%
“…1 No significant difference was found in the positive rate for pepsin in patients with functional heartburn or GERD with anxiety and depression (GERD-AD) compared to healthy controls. 1 Proton pump inhibitors reduced salivary pepsin concentration in patients with NERD and extraesophageal symptoms. 1 Their application of salivary pepsin to patients with GERD and GERD related diseases increase our understanding of its diagnostic role.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…6 Pepsin is present in gastric juice therefore, the presence of pepsin within the airways and salivary secretions makes pepsin an excellent biomarker for gastric reflux. [7][8][9] A need for a less invasive, rapid and cost-effective diagnostic test which is easily accessible to clinicians and more importantly for individuals to access for selfdiagnosing their reflux related symptoms led to the development of Peptest. Peptest uses lateral flow technology which contains two unique human pepsin monoclonal antibodies, one to detect pepsin and the other to capture pepsin.…”
Section: Introductionmentioning
confidence: 99%